Waste shell composite environment-friendly brake lining material and preparation method thereof

By using the combination of waste marine shell powder and other materials, an environmentally friendly automobile brake lining was prepared, which solved the carcinogenicity, noise pollution and high cost of existing materials, and achieved wear resistance, low noise and high heat stability performance, economical and environmentally friendly.

CN119192772APending Publication Date: 2024-12-27FUJIAN UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411383830.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing automotive brake lining materials have problems such as carcinogenicity, noise pollution, safety hazards and high production costs, and it is difficult to have good economic and environmental protection.

Method used

Use waste marine shell powder as the main material, combined with cellulose, composite fiber, glass fiber, resin, etc. to prepare environmentally friendly brake lining materials through calcining, grinding and hot press forming processes to reduce production costs and improve performance.

Benefits of technology

The brake lining with asbestos-free metal-free organic materials has the advantages of wear resistance, low dust loss, low noise, no rust, high heat stability and green environmental protection, reducing production costs and expanding market prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192772A_ABST
    Figure CN119192772A_ABST
Patent Text Reader

Abstract

The invention discloses a waste shell composite environment-friendly brake lining material and a preparation method of the waste shell composite environment-friendly brake lining material. Comprising 5-17% of waste shell powder, 3-10% of cellulose, 5-13% of composite fibers, 2-8% of glass fibers, 14-20% of resin, 3-5% of silicon-calcium powder, 2-5% of magnetite, 3-8% of nitrile rubber, 10-15% of graphite, 5-17% of barite powder and 10-17% of brake pad reclaimed materials. The waste shell composite environment-friendly brake lining material provided by the invention has the advantages of wear resistance, low dust fall, low noise and the like, the brake lining friction material is prepared from the waste marine shells, the raw material source is wide, the cost is low, the resource utilization of wastes is realized, the product cost is remarkably reduced on the premise of ensuring the brake performance of an automobile, and the economic benefit is high. The market prospect is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of brake linings, and in particular to a waste shell composite environmentally friendly brake lining material and a preparation method thereof. Background Art

[0002] Automobile brake lining refers to the friction material fixed on the brake drum or brake disc that rotates with the car wheel. It is composed of materials such as steel plate or ceramic, adhesive insulation layer and friction block. Brake lining friction material is a key component of automobile brakes, which determines the comfort, stability and safety of automobile driving. In recent years, the scale of China's automobile brake lining industry has grown steadily with the development of the automobile industry. With the increase in automobile ownership and sales, the scale of the automobile brake lining industry will further expand.

[0003] Automobile brake linings are generally composed of binders, reinforcing materials, fillers and friction performance modifiers. According to the materials, there are mainly asbestos type, semi-metal type, ceramic type and asbestos-free organic type brake linings. Asbestos fiber reinforced materials are cheap, but they are currently banned due to their carcinogenicity. Semi-metal and less-metal brake linings have good temperature control and high temperature resistance, but have high wear rate and noise pollution. Some metal fiber reinforced materials will release heavy metal oxides and some toxic gases during wear, posing a safety hazard. Ceramic brake linings are wear-resistant and high temperature-resistant, have good thermal stability and good braking performance, but the high price and complex production process limit their wide application.

[0004] With the rapid development of modern transportation industry, in addition to requiring brake linings to have necessary properties such as fast response speed, high thermal stability, good wear resistance, and low noise, brake lining materials are also required to have good economy and environmental protection. In recent years, it has become an important trend to use local regional characteristic environmentally friendly raw materials to prepare automobile brake lining friction materials, such as corn tangerines, palm kernel shells, cocoa beans, banana peels, bamboo charcoal, etc. Fujian is a coastal province with rich marine product resources. With the continuous expansion of the market demand for marine shellfish products, a large amount of shellfish waste has not been properly handled in the production and consumption links, causing environmental pollution, waste of resources and various safety hazards.

[0005] Based on this, the purpose of the present invention is to use discarded marine shells as a raw material for environmentally friendly brake lining friction materials, turning waste into treasure and reducing production costs while ensuring braking performance. Summary of the invention

[0006] In response to the above-mentioned problems, the present invention provides a waste shell composite environmentally friendly brake lining material and a preparation method thereof.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A waste shell composite environmentally friendly brake lining material, whose formula components, measured by weight percentage, include: 5-17% waste shell powder, 3-10% cellulose, 5-13% composite fiber, 2-8% glass fiber, 14-20% resin, 3%-5% calcium silicate powder, 2%-5% magnetite, 3-8% nitrile rubber, 10-15% graphite, 5-17% barite powder, and 10-17% brake pad recycled material.

[0009] As a possible implementation mode, further, the method for preparing the waste shell powder comprises the following steps:

[0010] The discarded shells are washed, dried and crushed, and the crushed shells are added into a heat treatment furnace for calcination. The calcined materials are then placed into a ball mill and ground with a silane coupling agent. After drying, the discarded shell powder raw material is obtained.

[0011] As a possible implementation mode, further, in the preparation process of the waste shell powder, the calcination temperature is 280-320°C, and the temperature is kept for 30 minutes; the waste shells are ground in a ball mill for 1-6 hours; and the silane coupling agent is KH550 or KH560.

[0012] As a possible implementation manner, further, the composite fiber is selected from the first composite fiber or the second composite fiber;

[0013] The first composite fiber comprises basalt fiber and cellulose fiber, wherein the cellulose fiber does not exceed 3%;

[0014] The second composite fiber includes basalt fiber, cellulose fiber, magnesium silicate fiber and aluminum silicate fiber, wherein the cellulose fiber does not exceed 3%, the magnesium silicate fiber does not exceed 5%, and the aluminum silicate fiber does not exceed 5%.

[0015] As a possible implementation manner, further, the resin is selected from phenolic resin.

[0016] As a possible implementation manner, further, the brake pad recycled material is NAO brake pad recycled material.

[0017] As a possible implementation mode, further, the method for preparing the waste shell composite environmentally friendly brake lining material comprises the following steps:

[0018] 1) The ingredients are prepared according to the formula of the waste shell composite environmentally friendly brake lining material, and are put into a screw mixer for stirring and mixing;

[0019] 2) placing the mixed raw materials in a disc or sheet mold and hot pressing them on a hot press;

[0020] 3) The formed lining is subjected to curing heat treatment in a heat treatment furnace, and the lining is cooled to a certain temperature and then taken out of the furnace for natural cooling to obtain the waste shell composite environmentally friendly brake lining material.

[0021] As a possible implementation manner, further, the stirring and mixing time in step 1) is 10-30 minutes.

[0022] As a possible implementation manner, further, in step 2), the hot pressing process is as follows: molding pressure 10-30 MPa, temperature 140-220° C., and holding time 5-10 minutes.

[0023] As a possible implementation mode, further, the curing heat treatment process in step 3) is: first heat to 120-160°C in a heat treatment furnace and keep warm for 2 hours, then heat to 160-200°C and keep warm for 6 hours, then cool to below 70°C in the furnace and cool naturally.

[0024] The beneficial effects of the present invention are as follows:

[0025] 1) The discarded marine shells in the present invention are widely available and low in cost, which can effectively reduce the production cost of brake linings and increase product added value.

[0026] 2) The environmentally friendly brake lining product prepared by the present invention using discarded marine shells is an asbestos-free and metal-free organic material, has the advantages of wear resistance, low dust, low noise, no rust, high thermal stability, green and environmental protection, etc., has good comprehensive performance and broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 A photo of discarded marine shells and their ground powder.

[0029] Figure 2 This is a physical picture of the environmentally friendly brake lining material composited with discarded shells. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] The present invention provides an environmentally friendly brake lining material composited with waste shells, the formula components of which, measured by weight percentage, include: 5-17% of waste shell powder, 3-10% of cellulose, 5-13% of composite fiber, 2-8% of glass fiber, 14-20% of phenolic resin, 3%-5% of calcium silicate powder, 2%-5% of magnetite, 3-8% of nitrile rubber, 10-15% of graphite, 5-17% of barite powder and 10-17% of NAO brake pad recycled material.

[0032] The above-mentioned composite fiber is selected from the first composite fiber or the second composite fiber; the first composite fiber includes basalt fiber and cellulose fiber, wherein the cellulose fiber does not exceed 3%; the second composite fiber includes basalt fiber, cellulose fiber, magnesium silicate fiber, and aluminum silicate fiber; wherein the cellulose fiber does not exceed 3%, the magnesium silicate fiber does not exceed 5%, and the aluminum silicate fiber does not exceed 5%.

[0033] The method for preparing waste shell powder comprises the following steps:

[0034] The discarded shells are washed, dried, and crushed, and calcined in a heat treatment furnace at a temperature of 280-320°C for 30 minutes; the calcined shell particles are placed in a ball mill and KH550 or KH560 silane coupling agent is added and ground for 1-6 hours, the shell powder is surface modified, and the discarded shell powder raw material is obtained after drying.

[0035] The method for preparing the above-mentioned waste shell composite environmentally friendly brake lining material comprises the following steps:

[0036] 1) The ingredients are prepared according to the formula of the waste shell composite environmentally friendly brake lining material, and put into a screw mixer for stirring and mixing for 10-30 minutes;

[0037] 2) Place the mixed raw materials in a disc or sheet mold and perform hot pressing molding on a hot press; the molding pressure is 10-30MPa, the temperature is 140-220°C, and the holding time is 5-10 minutes;

[0038] 3) The formed lining is subjected to curing heat treatment in a heat treatment furnace, and the process is as follows: firstly heated to 120-160°C in the heat treatment furnace and kept warm for 2 hours, then heated to 160-200°C and kept warm for 6 hours, and then cooled to below 70°C in the furnace and cooled naturally to obtain the waste shell composite environmentally friendly brake lining material.

[0039] Example 1

[0040] The formula components of the waste shell composite environmentally friendly brake lining material in this embodiment are: 17% waste shell powder, 3% cellulose, 13% composite fiber, 8% glass fiber, 14% phenolic resin, 3% calcium silicate powder, 2% magnetite, 6% nitrile rubber, 12.5% ​​graphite, 5% barite powder, and 16.5% NAO brake pad recycled material. Among them, the composite fiber is composed of basalt fiber and cellulose fiber, of which cellulose fiber accounts for 2%.

[0041] The preparation method of waste shell powder is as follows: washing, drying and crushing the waste shells, calcining them in a heat treatment furnace at a calcination temperature of 280-320°C and keeping them warm for 30 minutes; adding KH550 or KH560 silane coupling agent to the calcined shell particles in a ball mill for grinding for 1-6 hours, modifying the surface of the shell powder, and obtaining the waste shell powder raw material after drying.

[0042] The preparation method of the waste shell composite environmentally friendly brake lining material in this embodiment is as follows:

[0043] (1) Mixing

[0044] The ingredients are prepared according to the formula of the waste shell composite environmentally friendly brake lining material, and are put into a screw mixer for stirring and mixing for 10-30 minutes;

[0045] (2) Hot Pressing

[0046] Place the mixed raw materials in a disc or sheet mold and perform hot pressing molding on a hot press; the molding pressure is 10-30MPa, the temperature is 140-220℃, and the holding time is 5-10 minutes;

[0047] (3) Curing heat treatment

[0048] The formed lining is subjected to curing heat treatment in a heat treatment furnace, and the process is as follows: firstly heated to 120-160°C in the heat treatment furnace and kept warm for 2 hours, then heated to 160-200°C and kept warm for 6 hours, and then cooled to below 70°C in the furnace and cooled naturally to obtain the waste shell composite environmentally friendly brake lining material.

[0049] Example 2

[0050] The preparation method of the waste shell composite environmentally friendly brake lining material and the preparation method of waste shell powder in this embodiment are the same as those in Example 1, the only difference is that the formula components of the waste shell composite environmentally friendly brake lining material in this embodiment are: 13% waste shell powder, 6% cellulose, 13% composite fiber, 5% glass fiber, 16% phenolic resin, 5% calcium silicate powder, 2% magnetite, 4% nitrile rubber, 10% graphite, 9% barite powder, and 17% NAO brake pad recycled material. Among them, the composite fiber is composed of basalt fiber and cellulose fiber, of which cellulose fiber accounts for 3%.

[0051] Example 3

[0052] The preparation method of the waste shell composite environmentally friendly brake lining material and the preparation method of the waste shell powder in this embodiment are the same as those in Example 1, and the only difference is that the formula components of the waste shell composite environmentally friendly brake lining material in this embodiment are: 5% waste shell powder, 10% cellulose, 11% composite fiber, 3% glass fiber, 20% phenolic resin, 5% calcium silicate powder, 5% magnetite, 2% nitrile rubber, 12% graphite, 17% barite powder, and 10% NAO brake pad recycled material. Among them, the composite fiber is composed of basalt fiber, cellulose fiber, magnesium silicate fiber, and aluminum silicate fiber, of which cellulose fiber accounts for 2%, magnesium silicate fiber accounts for 4%, and aluminum silicate fiber accounts for 4%.

[0053] Product performance testing

[0054] The physical, mechanical and friction properties of the environmentally friendly composite brake lining materials made from discarded shells obtained in Examples 1-3 were tested respectively, and the testing method was as follows:

[0055] A) The hardness of the brake lining samples was measured using a HR-150A Rockwell hardness tester;

[0056] B) The impact strength of the brake lining samples was measured using an XJ-40 impact strength testing machine;

[0057] C) High and low temperature friction and wear tests were carried out on brake lining samples using an XD-MSM high and low temperature friction material testing machine.

[0058] The physical and mechanical properties experimental data of the waste shell composite environmentally friendly brake lining materials obtained in Examples 1-3 are shown in Table 1. From the data in Table 1, it can be seen that the physical and mechanical properties of the brake lining materials obtained in Examples 1-3 can meet the standard requirements.

[0059] Table 1 Experimental data on physical and mechanical properties of waste shell composite environmentally friendly brake lining materials

[0060] sample <![CDATA[Density (g / cm 3 )]]> Rockwell hardness (HRM) <![CDATA[Impact strength (J / cm 2 )]]> Standard requirements 1.90-2.10 60-90 ≥0.3 Example 1 2.01 87.5 0.43 Example 2 2.06 88 0.38 Example 3 2.07 90 0.35

[0061] The friction test data of the waste shell composite environmentally friendly brake lining materials obtained in Examples 1-3 are shown in Tables 2-4 below. It can be seen from the data in Tables 2-4 below that within the range of 100-300°C, the friction coefficient and wear rate of the brake lining materials obtained in Examples 1-3 remain stable, the wear rate is low, and the thermal decay resistance is good.

[0062] Table 2 Friction test data of waste shell composite environmentally friendly brake lining material obtained in Example 1

[0063]

[0064] Table 3 Friction test data of waste shell composite environmentally friendly brake lining material obtained in Example 2

[0065]

[0066] Table 4 Friction test data of waste shell composite environmentally friendly brake lining material obtained in Example 3

[0067]

[0068] In summary, the brake lining material of the present invention uses discarded marine shells as a raw material for preparing environmentally friendly brake linings, and has the advantages of wear resistance, low dust, low noise, no rust, high thermal stability, green environmental protection, etc. Discarded marine shells have a wide source and low cost, which can effectively reduce the production cost of brake linings, increase product added value, and have broad market prospects.

[0069] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A waste shell composite environmentally friendly brake lining material, characterized in that: The formula components, calculated by weight percentage, include: 5-17% waste shell powder, 3-10% cellulose, 5-13% composite fiber, 2-8% glass fiber, 14-20% resin, 3%-5% calcium silicate powder, 2%-5% magnetite, 3-8% nitrile rubber, 10-15% graphite, 5-17% barite powder, and 10-17% brake pad recycled material.

2. The waste shell composite environmentally friendly brake lining material according to claim 1 is characterized in that: The method for preparing the waste shell powder comprises the following steps: The discarded shells are washed, dried and crushed, and the crushed shells are added into a heat treatment furnace for calcination. The calcined materials are then placed into a ball mill and ground with a silane coupling agent. After drying, the discarded shell powder raw material is obtained.

3. The waste shell composite environmentally friendly brake lining material according to claim 1 is characterized in that: During the preparation of the waste shell powder, the calcination temperature is 280-320° C. and the temperature is kept for 30 minutes; the waste shells are ground in a ball mill for 1-6 hours; and the silane coupling agent is KH550 or KH560.

4. The waste shell composite environmentally friendly brake lining material according to claim 1, characterized in that: The composite fiber is selected from the first composite fiber or the second composite fiber; The first composite fiber comprises basalt fiber and cellulose fiber, wherein the cellulose fiber does not exceed 3%; The second composite fiber includes basalt fiber, cellulose fiber, magnesium silicate fiber, and aluminum silicate fiber; The content of cellulose fiber shall not exceed 3%, magnesium silicate fiber shall not exceed 5%, and aluminum silicate fiber shall not exceed 5%.

5. The waste shell composite environmentally friendly brake lining material according to claim 1, characterized in that: The resin is selected from phenolic resin.

6. The waste shell composite environmentally friendly brake lining material according to claim 1, characterized in that: The brake pad recycled material is NAO brake pad recycled material.

7. The waste shell composite environmentally friendly brake lining material according to claim 1, characterized in that: The method for preparing the waste shell composite environmentally friendly brake lining material comprises the following steps: 1) preparing the ingredients according to the formula of the waste shell composite environmentally friendly brake lining material, and putting them into a screw mixer for stirring and mixing; 2) placing the mixed raw materials in a disc or sheet mold and hot pressing them on a hot press; 3) The formed lining is subjected to curing heat treatment in a heat treatment furnace, and is cooled to a certain temperature and then taken out of the furnace for natural cooling to obtain the waste shell composite environmentally friendly brake lining material.

8. The waste shell composite environmentally friendly brake lining material according to claim 7, characterized in that: The stirring and mixing time in step 1) is 10-30 minutes.

9. The waste shell composite environmentally friendly brake lining material according to claim 7, characterized in that: The hot pressing process in step 2) is: molding pressure 10-30MPa, temperature 140-220°C, and holding time 5-10 minutes.

10. The waste shell composite environmentally friendly brake lining material according to claim 7, characterized in that: The curing heat treatment process in step 3) is: first heat to 120-160°C in a heat treatment furnace and keep warm for 2 hours, then heat to 160-200°C and keep warm for 6 hours, then cool to below 70°C in the furnace and cool naturally.